Arbitraje de inversiones versus arbitraje Uncitral: un análisis desde la perspectiva procesal - Aliste Santos, Tomás J. (2024)
For more than sixty years, international investment law has become an extraordinary way to generate legal certainty in the economic development of an increasingly global world. In this sense, investment treaties have contributed through the incorporation of ISDS clauses to offer a framework for the resolution of investment disputes between international business corporations and the various States, which offers guarantees of neutrality and procedural security in the management of the conflict. In this article, we offer a critical analysis of investment arbitration. Based on the comparative analysis, we appreciate notable differences between UNCITRAL arbitration and investment arbitration, pointing out some problems of the current investment arbitration model.